2020
DOI: 10.1039/d0cc01726d
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature molten salt synthesis of MoS2@CoS2 heterostructures for efficient hydrogen evolution reaction

Abstract: A facile low-temperature molten salt approach has been successfully developed to construct MoS2@CoS2 heterostructures for high-efficiency hydrogen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…[29,30] Pristine MoS 2 exhibits Chemistry-A European Journal microspheres morphology consisting of typical thin nanosheets (Figures 1c and S3), and CoS 2 /MoS 2 heterostructure shows a spherelike morphology without agglomeration and coalescence, thereby maximally exposing the edge sites (Figure 1d). [31] Meanwhile, CoS 2 /MoS 2 /PDDA-rGO and CoS 2 /MoS 2 /PDDA-rGO/ PMo 12 show that the surface of PDDA-rGO was evenly covered by different morphology CoS 2 /MoS 2 nanoarrays, due to the influence of PDDA-rGO (Figures 1e and 1 f). And similar morphological features were also applicable to MoS 2 /PDDA-rGO (Figure S4).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…[29,30] Pristine MoS 2 exhibits Chemistry-A European Journal microspheres morphology consisting of typical thin nanosheets (Figures 1c and S3), and CoS 2 /MoS 2 heterostructure shows a spherelike morphology without agglomeration and coalescence, thereby maximally exposing the edge sites (Figure 1d). [31] Meanwhile, CoS 2 /MoS 2 /PDDA-rGO and CoS 2 /MoS 2 /PDDA-rGO/ PMo 12 show that the surface of PDDA-rGO was evenly covered by different morphology CoS 2 /MoS 2 nanoarrays, due to the influence of PDDA-rGO (Figures 1e and 1 f). And similar morphological features were also applicable to MoS 2 /PDDA-rGO (Figure S4).…”
Section: Resultsmentioning
confidence: 93%
“…Meanwhile, the selected area electron diffraction (SAED) pattern of PDDA‐rGO indicates isolate exfoliated graphene nanosheets in a highly‐crystallized and hexagonal structure (Figure 1b) [29,30] . Pristine MoS 2 exhibits microspheres morphology consisting of typical thin nanosheets (Figures 1c and S3), and CoS 2 /MoS 2 heterostructure shows a spherelike morphology without agglomeration and coalescence, thereby maximally exposing the edge sites (Figure 1d) [31] . Meanwhile, CoS 2 /MoS 2 /PDDA‐rGO and CoS 2 /MoS 2 /PDDA‐rGO/PMo 12 show that the surface of PDDA‐rGO was evenly covered by different morphology CoS 2 /MoS 2 nanoarrays, due to the influence of PDDA‐rGO (Figures 1e and 1 f).…”
Section: Resultsmentioning
confidence: 99%
“…Nanosheets of Ru-MoS 2-x -CoS 2 /CC are also clearly observed from transmission electron microscopic (TEM) image ( Figure 2E ), which is consistent with the results of SEM images. According to the high-resolution TEM (HR-TEM) image ( Figure 2F ), the lattice spacings of 0.625 and 0.245 nm that are seen in Ru-MoS 2-x -CoS 2 /CC correspond to the (002) plane of MoS 2 and the (210) plane of CoS 2 ( He et al, 2020 ; Liu X. et al, 2022 ), respectively. These also conform to the results of XRD.…”
Section: Resultsmentioning
confidence: 99%
“…So, high-efficiency and stable OER catalysts can be the key factor to accelerate reaction rate and improve energy conversion efficiency. [2] Currently, precious metal catalysts (such as Ir, Ru and Pd) have been demonstrated that they can prove the reaction rates and low the overpotentials of OER. But the high price of these metals limits the large-scale applications of water splitting.…”
Section: Introductionmentioning
confidence: 99%